1993
DOI: 10.1007/bf03348862
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid stimulation by placental factors

Abstract: There is now convincing evidence that the human placenta produces factors which have some role in regulating maternal thyroid function during normal pregnancy and are capable of inducing overt hyperthyroidism in some pregnant women and in patients with trophoblastic tumors. As far as the biochemical nature of these placental thyroid stimulators is concerned, a bulk of evidence indicates that hCG, which is abundant in the blood of pregnant women and patients with trophoblastic diseases and shares some structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It has since been amply confirmed that in various pathological conditions, such as molar pregnancy (104,105), other trophoblastic disease (choriocarcinoma) (106 -109), and cancers of various origins (110 -113), elevated hCG levels could induce hyperthyroidism, characterized by the rapid appearance of thyrotoxic symptoms and their even more rapid disappearance after the surgical removal of the mole or cure of the tumor. Taken together, these observations have led to the concept that a substance secreted during pregnancy, and at particularly high levels in moles and choriocarcinomas, could be responsible for hyperthyroidism.…”
Section: Regulation Of Serum Tshmentioning
confidence: 98%
“…It has since been amply confirmed that in various pathological conditions, such as molar pregnancy (104,105), other trophoblastic disease (choriocarcinoma) (106 -109), and cancers of various origins (110 -113), elevated hCG levels could induce hyperthyroidism, characterized by the rapid appearance of thyrotoxic symptoms and their even more rapid disappearance after the surgical removal of the mole or cure of the tumor. Taken together, these observations have led to the concept that a substance secreted during pregnancy, and at particularly high levels in moles and choriocarcinomas, could be responsible for hyperthyroidism.…”
Section: Regulation Of Serum Tshmentioning
confidence: 98%
“…It has also been shown that serum human chorionic gonadotrophin, with its marked elevation in early pregnancy, may directly stimulate the thyroid gland through its TSH-like activity. 14 Moreover, oestrogen receptors have been demonstrated in thyroid cancers, particularly in well-differentiated carcinomas and oestrogen has been shown to promote thyroid tumors in animal models. 15,16 Based on the findings from descriptive and analytical epidemiology, laboratory and animal studies and individual case reports, there is sufficient evidence to suggest that hormonal and biochemical changes related to reproductive events and patterns could be relevant to the etiology of benign thyroid dysfunction or disease and neoplasia.…”
mentioning
confidence: 99%
“… 95 Maternal PFHxS in pregnancy was negatively associated with thyroxine (T4) in 726 pregnancies, 90 and hCG regulates maternal thyroid hormone production in the first trimester. 96 , 97 …”
Section: Discussionmentioning
confidence: 99%